Simplified pulmonary embolism severity index is associated with recurrent venous thromboembolism in patients with pulmonary embolism. Issue 3 (5th February 2021) - Zhang, Jia-Rui; Zhou, Chen; Zhou, Hai-Xia; Li, Xiao-Qian; Hu, Yue-Hong; Wang, Mao-Yun; Tang, Yong-Jiang; Yi, Qun
Abstract : Supplemental Digital Content is available in the text